How do they interact? Exploring issues of interaction forms in an online writing classroom - Anak Agung Putri Maharani; Made Hery Santosa (Studies in English Language and Education, 2025)
As the 21st century progresses, there is a growing emphasis on equipping students with essential skills, including writing, which is considered crucial to master. Online writing has become particularly significant in fostering this skill, as advanced technology enhances classroom activities and creates new opportunities for interaction between lecturers and students. This study aimed to assess the levels of six types of interaction, identify the forms of interaction students value most, determine the forms most frequently conducted by lecturers, and explore the benefits of these interactions in an online writing course. This study utilized a sequential explanatory design involving 122 respondents. Data were collected using two research instruments: a questionnaire and interviews. The findings revealed that respondents demonstrated two preferences for a high level of interaction, both of which showed a notable increase in the six forms of interaction. Among these, four types of interaction were perceived by students as playing a critical role in their online writing activities. However, only three forms of interaction were identified as being frequently implemented by the lecturer, reflecting an emphasis on student-centred learning. Each type of interaction was acknowledged as contributing distinct benefits to the students. This study underlines the importance of adopting diverse and student-centred interactions in online writing courses to enhance student engagement and learning outcomes.